Traditional & New Media of Mass Communication: Blending Traditions and Modernity: Television, Education and Life-Skills orientation of Urban Youths in Uganda - Kakembo, Frederick; Kibuka musoke, Martha (Journal of Communication and Media Research, 2017)
This paper explores opportunities and constraints of using television for enhancement of lifeskills orientation for urban youths in Uganda. In the wave of rapid urbanization, globalization and mobility, African socio-cultural institutions continue to be eroded and the urban youths need alternative frameworks of support to orient them into responsible adults. Creative use of television could be central in imparting the requisite skills for living in the 21st century. Despite its great attributes and abundance in urban homesteads, television has not played a central educational role in the lives of the urban youths. A qualitative study approach was undertaken to determine constraints in the use of television for education and development communication. Focus group discussions, content analysis, in-depth interviews, documents analysis and reviews of recent studies were used to collect data. Findings reveal that television as a medium offers great opportunities for life-skills orientation for the urban youths. The failure to optimally use the medium is attributed to technical and epistemological factors on part of educators and communicators. Recommendations are offered to optimally utilize use this abundant and attractive medium for life-skills orientation
Keywords: Mass Communication; Modernity